Honey and its role in developing Lombok and Sumbawa islands as destinations for traditional health tourism based on Sasambo culture - Aliefman Hakim; Jamaluddin Jamaluddin; Syarifa Wahidah Al Idrus (Jurnal Pijar Mipa, 2021)
The development of tourism is currently a priority for governments in Indonesia. Apart from natural beauty, traditional health tourism by utilizing local products has begun to be developed. The islands of Lombok and Sumbawa have a wealth of honey with extraordinary properties. It has been promoted as one of the first steps in promoting tourism from the traditional health sector. Efforts are made to improve the quality of Lombok and Sumbawa as a traditional health tourism destination based on the Sasambo culture (indigenous culture of the islands of Lombok and Sumbawa). The use of honey with its various health benefits can support traditional health tourism on the islands of Lombok and Sumbawa. Apart from providing good health benefits for the public or tourists, both local and foreign, honey is also able to support the regional economy. Honey from the islands of Lombok and Sumbawa can be used as a superior product for souvenirs and educational products related to traditional health, increasing tourists' desire to visit the islands of Lombok and Sumbawa with their special types of honey.